MgO ceramic material prepared by low-temperature sintering and preparation method thereof

CN118930229BActive Publication Date: 2026-10-27HUNAN UNIV OF TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410908162.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-08
Publication Date
2026-10-27
Estimated Expiration
2044-07-08

AI Technical Summary

Technical Problem

[0006]本发明为克服现有MgO陶瓷烧结温度高、低温度烧结不能够致密的问题,提供了一种低温烧结制备的MgO陶瓷材料及其制备方法

Benefits of technology

[0024]本发明在MgO陶瓷中添加Al2O3和MgF2,利用MgF2降低混合物的熔点,以及Al2O3能够固溶提升MgO陶瓷的烧结性能,使孔隙数量与尺寸降低并且MgF2还能降低MgAl2O4相的形成温度,MgAl2O4相能够代替Al2O3填充在MgO的晶粒之间,使颗粒更加紧密,两者协同,能够大幅度减低MgO陶瓷的烧成温度

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118930229B_ABST
    Figure CN118930229B_ABST
Patent Text Reader

Abstract

The application discloses a kind of MgO ceramic materials and preparation method of low-temperature sintering preparation, and the application is by adding alumina and magnesium fluoride in magnesium oxide ceramic, using MgF2 can reduce the sintering temperature of mixture and Al2O3 can make porosity quantity and size reduce, improve the density of MgO, reduce the temperature of MgO ceramic, make MgO ceramic can be dense at low temperature.The application also mixes MgO powder with monomer, crosslinking agent, dispersing agent and the like, makes MgO gel state liquid homogenization, avoids the agglomeration of magnesium oxide, the sintering temperature of the method described in the application is lower, reduces energy consumption, shortens experimental period, the density of MgO ceramic is more than 90%, with excellent mechanical properties and good thermal conductivity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of magnesium oxide thermally conductive ceramic technology, and more specifically, relates to a MgO ceramic material prepared by low-temperature sintering and its preparation method. Background Technology

[0002] Magnesium oxide ceramics are widely used in high-tech and high-precision fields due to their excellent properties such as high strength, corrosion resistance, and wear resistance. However, the production of high-quality magnesium oxide ceramics faces the following challenges:

[0003] (1) During the manufacturing process, magnesium oxide powder easily absorbs moisture from the air and agglomerates, which affects the flowability of the powder and makes it difficult to disperse the powder evenly.

[0004] (2) Sintering of magnesium oxide ceramics requires temperatures above 1700℃, which is not only costly, but also makes it difficult to control the crystal phase. The resulting green body has a loose structure, low strength, and poor thermal conductivity.

[0005] To address the aforementioned issues, CN104276815B discloses an oxide ceramic material and its preparation method, which uses 70%–96% magnesium oxide, 2%–25% aluminum oxide, 0.2%–1.2% silicon dioxide, 0.2%–2.5% calcium oxide, 0.1%–0.5% iron oxide, and 0.5%–1.5% zircon as raw material components. Through ball milling, wax mixing, molding, initial firing, green body trimming, firing, and post-processing, a novel high thermal conductivity ceramic material with a sintering temperature of only 1650℃ is obtained. This patent utilizes the transformation of magnesium oxide and aluminum oxide from a tetragonal to a cubic crystal phase. Zirconia, during this phase transformation, expands and then contracts, adapting to the volume changes during phase transformations of other materials. This reduces crystal dislocations and porosity, enhancing the damage tolerance of the material during sintering, inhibiting or preventing crack propagation, and increasing the density and fracture toughness of magnesium oxide ceramics. Furthermore, it utilizes silica and calcium oxide to lower the sintering temperature and provides high acid resistance, improving the product's resistance to acid corrosion. Although this method lowers the sintering temperature through silica and calcium oxide, a sintering temperature above 1600℃ is still required. Without reaching this temperature, the magnesium oxide ceramic cannot maintain its high density. Summary of the Invention

[0006] To overcome the problems of high sintering temperature and insufficient densification of existing MgO ceramics, this invention provides a MgO ceramic material prepared by low-temperature sintering and its preparation method.

[0007] This invention is achieved through the following technical solution:

[0008] A MgO ceramic material prepared by low-temperature sintering, comprising magnesium oxide, aluminum oxide and magnesium fluoride as raw materials, wherein the mass ratio of magnesium oxide, aluminum oxide and magnesium fluoride is 95:5:3-5.

[0009] A method for preparing MgO ceramic materials by low-temperature sintering, comprising the following steps:

[0010] S1. Mix magnesium oxide, aluminum oxide and magnesium fluoride powders evenly according to the mass ratio to obtain a mixed powder;

[0011] S2. Mix the mixed powder with organic matter to obtain a mixed slurry, and then vacuum process the mixed slurry to obtain MgO gel liquid;

[0012] S3. After drying the MgO gel liquid, a green body is obtained, then dehydrated at 50-160℃, and then heated to 500℃ for degreasing.

[0013] S4. The degreased green body is heated to 1400-1450℃ for sintering, and after cooling, MgO ceramic material prepared by low-temperature sintering is obtained.

[0014] Furthermore, the mixed powder is pretreated by acid solution purification and ball milling, which can effectively remove oxides in the original powder that affect the thermal conductivity of the material and improve the surface energy and sintering activity of the powder, thereby increasing the uniformity of the mixing of MgO powder and sintering aid.

[0015] Furthermore, the acidic solution includes one or more of HNO3, HCl, H2SO4, and acetic acid, with a solution concentration of 2-5%.

[0016] Furthermore, the mass ratio of the mixed powder to the organic matter is 2.5 to 3:1.

[0017] Furthermore, the organic compound includes monomers, crosslinking agents, dispersants, and catalysts in a mass ratio of 8:2:1:1.

[0018] Further, the monomer is one or more of acrylic acid, dimethacrylamide, dimethylaminoisobutylene acid, methacrylate, and hydroxyethyl acrylate; the crosslinking agent is one or more of N,N-methyleneacrylamide and isocyanate; and the catalyst is one or more of tetramethylethylenediamine, Lewis acid, and polyacrylamide.

[0019] Furthermore, the dehydration treatment includes holding at 50℃, 80℃, 120℃ and 160℃ for 2 to 3 hours respectively.

[0020] Furthermore, the heating and degreasing process is carried out at 500°C for 2-3 hours.

[0021] Furthermore, the heating rate of the dehydration treatment is 5-10℃ / min; the heating rate of the degreasing treatment is 1-5℃ / min.

[0022] Furthermore, the sintering heating rate is 1–5 °C / min, and the holding time is 2–3 h.

[0023] Compared with existing technologies, the beneficial effects are:

[0024] This invention adds Al2O3 and MgF2 to MgO ceramics. MgF2 lowers the melting point of the mixture, and Al2O3's solid solution properties improve the sintering performance of MgO ceramics, reducing the number and size of pores. Furthermore, MgF2 lowers the formation temperature of the MgAl2O4 phase, which can replace Al2O3 and fill the spaces between MgO grains, resulting in a more compact particle structure. The synergistic effect of these two components significantly reduces the firing temperature of MgO ceramics.

[0025] This invention mixes raw materials such as MgO with polymer monomers, and obtains an MgO gel liquid through crosslinking. After drying, a green body is obtained, which effectively ensures the dispersion of MgO and avoids MgO agglomeration. By controlling the raw material combination and sintering at a temperature of 1400-1450℃, MgO ceramics with excellent mechanical properties and good thermal conductivity can be obtained. Attached Figure Description

[0026] Figure 1 SEM images of the sintered samples: (a) SEM image of 3% MgF2 at 1400℃; (b) SEM image of 4% MgF2 at 1400℃; (c) SEM image of 5% MgF2 at 1400℃; (d) SEM image of 3% MgF2 at 1450℃; (e) SEM image of 4% MgF2 at 1450℃; (f) SEM image of 5% MgF2 at 1450℃.

[0027] Figure 2 The XRD pattern of the sample after calcination at 1400℃ is shown.

[0028] Figure 3 The XRD pattern of the sample after calcination at 1450℃ is shown. Detailed Implementation

[0029] The following examples further explain and clarify the invention, but the specific examples do not limit the invention in any way. Unless otherwise specified, the methods and equipment used in the examples are conventional methods and equipment in the art, and the raw materials used are all commercially available.

[0030] Example 1

[0031] This embodiment provides a MgO ceramic material prepared by low-temperature sintering, the steps of which include:

[0032] S1. Preprocessing

[0033] Magnesium oxide powder, aluminum oxide powder, and magnesium fluoride powder were weighed out in a mass ratio of 95:5:3 and mixed. Then, some impurities were removed in an acidic solution with a concentration of 2-5%, which increased the surface activity of the mixed powder and made the mixed powder evenly dispersed.

[0034] S2. Preparation of gel-like liquid

[0035] The mixed powder was ball-milled with anhydrous ethanol, and then dried and sieved to obtain MgO powder. The MgO powder was then thoroughly mixed with an organic compound containing monomers, crosslinking agents, dispersants, and catalysts in a ratio of 3:1, wherein the mass ratio of monomers, crosslinking agents, dispersants, and catalysts was 8:2:1:1. The mixed slurry was then vacuum-treated to obtain MgO gel liquid.

[0036] S3. Drying and shaping

[0037] Pour the MgO gel liquid into a mold and place the mold in an oven. Dry the MgO gel liquid at 50°C for 2 hours. The gel liquid undergoes a physicochemical reaction in the mold to generate a green body with a certain strength.

[0038] S4. Dehydration and degreasing

[0039] The billet was placed in a muffle furnace and heated from room temperature to 50°C, 80°C, 120°C, and 160°C at a rate of 5°C / min, and held at each temperature for 3 hours to dehydrate the billet. Then, it was heated from 160°C to 500°C at a rate of 1°C / min and held for 2 hours to degrease.

[0040] S5. Sintering

[0041] Finally, the temperature was increased from 500℃ to 1000℃ at a rate of 5℃ / min and held for 20 min, then increased from 1000℃ to 1400℃ at a rate of 5℃ / min and held for 3 h. The furnace was then cooled to room temperature to obtain the MgO ceramic material prepared by low-temperature sintering.

[0042] Example 2

[0043] This embodiment provides a MgO ceramic material prepared by low-temperature sintering, the steps of which include:

[0044] S1. Preprocessing

[0045] Magnesium oxide powder, aluminum oxide powder, and magnesium fluoride powder were weighed out in a mass ratio of 95:5:4 and mixed. Then, some impurities were removed in an acidic solution with a concentration of 2-5%, which increased the surface activity of the mixed powder and made the mixed powder evenly dispersed.

[0046] S2. Preparation of gel-like liquid

[0047] The mixed powder was ball-milled with anhydrous ethanol, and then dried and sieved to obtain MgO powder. The MgO powder was then thoroughly mixed with an organic compound containing monomers, crosslinking agents, dispersants, and catalysts in a ratio of 3:1, wherein the mass ratio of monomers, crosslinking agents, dispersants, and catalysts was 8:2:1:1. The mixed slurry was then vacuum-treated to obtain MgO gel liquid.

[0048] S3. Drying and shaping

[0049] Pour the MgO gel liquid into a mold and place the mold in an oven. Dry the MgO gel liquid at 50°C for 2 hours. The gel liquid undergoes a physicochemical reaction in the mold to generate a green body with a certain strength.

[0050] S4. Dehydration and degreasing

[0051] The billet was placed in a muffle furnace and heated from room temperature to 50°C, 80°C, 120°C, and 160°C at a rate of 5°C / min, and held at each temperature for 3 hours to dehydrate the billet. Then, it was heated from 160°C to 500°C at a rate of 1°C / min and held for 2 hours to degrease.

[0052] S5. Sintering

[0053] Finally, the temperature was increased from 500℃ to 1000℃ at a rate of 5℃ / min and held for 20 min, then increased from 1000℃ to 1400℃ at a rate of 5℃ / min and held for 3 h. The furnace was then cooled to room temperature to obtain the MgO ceramic material prepared by low-temperature sintering.

[0054] Example 3

[0055] This embodiment provides a MgO ceramic material prepared by low-temperature sintering, the steps of which include:

[0056] S1. Preprocessing

[0057] Magnesium oxide powder, aluminum oxide powder, and magnesium fluoride powder were weighed out in a mass ratio of 95:5:5 and mixed. Then, some impurities were removed in an acidic solution with a concentration of 2-5%, which increased the surface activity of the mixed powder and made the mixed powder evenly dispersed.

[0058] S2. Preparation of gel-like liquid

[0059] The mixed powder was ball-milled with anhydrous ethanol, and then dried and sieved to obtain MgO powder. The MgO powder was then thoroughly mixed with an organic compound containing monomers, crosslinking agents, dispersants, and catalysts in a ratio of 3:1, wherein the mass ratio of monomers, crosslinking agents, dispersants, and catalysts was 8:2:1:1. The mixed slurry was then vacuum-treated to obtain MgO gel liquid.

[0060] S3. Drying and shaping

[0061] Pour the MgO gel liquid into a mold and place the mold in an oven. Dry the MgO gel liquid at 50°C for 2 hours. The gel liquid undergoes a physicochemical reaction in the mold to generate a green body with a certain strength.

[0062] S4. Dehydration and degreasing

[0063] The billet was placed in a muffle furnace and heated from room temperature to 50°C, 80°C, 120°C, and 160°C at a rate of 5°C / min, and held at each temperature for 3 hours to dehydrate the billet. Then, it was heated from 160°C to 500°C at a rate of 1°C / min and held for 2 hours to degrease.

[0064] S5. Sintering

[0065] Finally, the temperature was increased from 500℃ to 1000℃ at a rate of 5℃ / min and held for 20 min, then increased from 1000℃ to 1400℃ at a rate of 5℃ / min and held for 3 h. The furnace was then cooled to room temperature to obtain the MgO ceramic material prepared by low-temperature sintering.

[0066] Example 4

[0067] This embodiment provides a MgO ceramic material prepared by low-temperature sintering, the steps of which include:

[0068] S1. Preprocessing

[0069] Magnesium oxide powder, aluminum oxide powder, and magnesium fluoride powder were weighed out in a mass ratio of 95:5:3 and mixed. Then, some impurities were removed in an acidic solution with a concentration of 2-5%, which increased the surface activity of the mixed powder and made the mixed powder evenly dispersed.

[0070] S2. Preparation of gel-like liquid

[0071] The mixed powder was ball-milled with anhydrous ethanol, and then dried and sieved to obtain MgO powder. The MgO powder was then thoroughly mixed with an organic compound containing monomers, crosslinking agents, dispersants, and catalysts in a ratio of 3:1, wherein the mass ratio of monomers, crosslinking agents, dispersants, and catalysts was 8:2:1:1. The mixed slurry was then vacuum-treated to obtain MgO gel liquid.

[0072] S3. Drying and shaping

[0073] Pour the MgO gel liquid into a mold and place the mold in an oven. Dry the MgO gel liquid at 50°C for 2 hours. The gel liquid undergoes a physicochemical reaction in the mold to generate a green body with a certain strength.

[0074] S4. Dehydration and degreasing

[0075] The billet was placed in a muffle furnace and heated from room temperature to 50°C, 80°C, 120°C, and 160°C at a rate of 5°C / min, and held at each temperature for 3 hours to dehydrate the billet. Then, it was heated from 160°C to 500°C at a rate of 1°C / min and held for 2 hours to degrease.

[0076] S5. Sintering

[0077] Finally, the temperature was increased from 500℃ to 1000℃ at a rate of 5℃ / min and held for 20 min, then increased from 1000℃ to 1450℃ at a rate of 5℃ / min and held for 3 h. The furnace was then cooled to room temperature to obtain the MgO ceramic material prepared by low-temperature sintering.

[0078] Example 5

[0079] This embodiment provides a MgO ceramic material prepared by low-temperature sintering, the steps of which include:

[0080] S1. Preprocessing

[0081] Magnesium oxide powder, aluminum oxide powder, and magnesium fluoride powder were weighed out in a mass ratio of 95:5:4 and mixed. Then, some impurities were removed in an acidic solution with a concentration of 2-5%, which increased the surface activity of the mixed powder and made the mixed powder evenly dispersed.

[0082] S2. Preparation of gel-like liquid

[0083] The mixed powder was ball-milled with anhydrous ethanol, and then dried and sieved to obtain MgO powder. The MgO powder was then thoroughly mixed with monomers, crosslinking agents, dispersants, and catalysts in a specific ratio, and the mixture was then vacuum-treated to obtain MgO gel liquid.

[0084] S3. Drying and shaping

[0085] Pour the MgO gel liquid into a mold and place the mold in an oven. Dry the MgO gel liquid at 50°C for 2 hours. The gel liquid undergoes a physicochemical reaction in the mold to generate a green body with a certain strength.

[0086] S4. Dehydration and degreasing

[0087] The billet was placed in a muffle furnace and heated from room temperature to 50°C, 80°C, 120°C, and 160°C at a rate of 5°C / min, and held at each temperature for 3 hours to dehydrate the billet. Then, it was heated from 160°C to 500°C at a rate of 1°C / min and held for 2 hours to degrease.

[0088] S5. Sintering

[0089] Finally, the temperature was increased from 500℃ to 1000℃ at a rate of 5℃ / min and held for 20 min, then increased from 1000℃ to 1450℃ at a rate of 5℃ / min and held for 3 h. The furnace was then cooled to room temperature to obtain the MgO ceramic material prepared by low-temperature sintering.

[0090] Example 6

[0091] This embodiment provides a MgO ceramic material prepared by low-temperature sintering, the steps of which include:

[0092] S1. Preprocessing

[0093] Magnesium oxide powder, aluminum oxide powder, and magnesium fluoride powder were weighed out in a mass ratio of 95:5:5 and mixed. Then, some impurities were removed in an acidic solution with a concentration of 2-5%, which increased the surface activity of the mixed powder and made the mixed powder evenly dispersed.

[0094] S2. Preparation of gel-like liquid

[0095] The mixed powder was ball-milled with anhydrous ethanol, and then dried and sieved to obtain MgO powder. The MgO powder was then thoroughly mixed with an organic compound containing monomers, crosslinking agents, dispersants, and catalysts in a ratio of 3:1, wherein the mass ratio of monomers, crosslinking agents, dispersants, and catalysts was 8:2:1:1. The mixed slurry was then vacuum-treated to obtain MgO gel liquid.

[0096] S3. Drying and shaping

[0097] Pour the MgO gel liquid into a mold and place the mold in an oven. Dry the MgO gel liquid at 50°C for 2 hours. The gel liquid undergoes a physicochemical reaction in the mold to generate a green body with a certain strength.

[0098] S4. Dehydration and degreasing

[0099] The billet was placed in a muffle furnace and heated from room temperature to 50°C, 80°C, 120°C, and 160°C at a rate of 5°C / min, and held at each temperature for 3 hours to dehydrate the billet. Then, it was heated from 160°C to 500°C at a rate of 1°C / min and held for 2 hours to degrease.

[0100] S5. Sintering

[0101] Finally, the temperature was increased from 500℃ to 1000℃ at a rate of 5℃ / min and held for 20 min, then increased from 1000℃ to 1450℃ at a rate of 5℃ / min and held for 3 h. The furnace was then cooled to room temperature to obtain the MgO ceramic material prepared by low-temperature sintering.

[0102] Comparative Example 1

[0103] This embodiment provides a MgO ceramic material prepared by low-temperature sintering, the steps of which include:

[0104] S1. Preprocessing

[0105] Magnesium oxide powder and magnesium fluoride powder with a mass ratio of 95:4 were weighed and mixed. Then, some impurities were removed in an acidic solution with a concentration of 2-5%, which increased the surface activity of the mixed powder and made the mixed powder evenly dispersed.

[0106] S2. Preparation of gel-like liquid

[0107] The mixed powder was ball-milled with anhydrous ethanol, and then dried and sieved to obtain MgO powder. The MgO powder was then thoroughly mixed with an organic compound containing monomers, crosslinking agents, dispersants, and catalysts in a ratio of 3:1, wherein the mass ratio of monomers, crosslinking agents, dispersants, and catalysts was 8:2:1:1. The mixed slurry was then vacuum-treated to obtain MgO gel liquid.

[0108] S3. Drying and shaping

[0109] Pour the MgO gel liquid into a mold and place the mold in an oven. Dry the MgO gel liquid at 50°C for 2 hours. The gel liquid undergoes a physicochemical reaction in the mold to generate a green body with a certain strength.

[0110] S4. Dehydration and degreasing

[0111] The billet was placed in a muffle furnace and heated from room temperature to 50°C, 80°C, 120°C, and 160°C at a rate of 5°C / min, and held at each temperature for 3 hours to dehydrate the billet. Then, it was heated from 160°C to 500°C at a rate of 1°C / min and held for 2 hours to degrease.

[0112] S5. Sintering

[0113] Finally, the temperature was increased from 500℃ to 1000℃ at a rate of 5℃ / min and held for 20 min, then increased from 1000℃ to 1400℃ at a rate of 5℃ / min and held for 170–190 min. The furnace was then cooled to room temperature to obtain the MgO ceramic material prepared by low-temperature sintering.

[0114] Comparative Example 2

[0115] This embodiment provides a MgO ceramic material prepared by low-temperature sintering, the steps of which include:

[0116] S1. Preprocessing

[0117] Magnesium oxide powder and aluminum oxide powder with a mass ratio of 95:5 were weighed and mixed. Then, some impurities were removed in an acidic solution with a concentration of 2-5%, which increased the surface activity of the mixed powder and made the mixed powder evenly dispersed.

[0118] S2. Preparation of gel-like liquid

[0119] The mixed powder was ball-milled with anhydrous ethanol, and then dried and sieved to obtain MgO powder. The MgO powder was then thoroughly mixed with an organic compound containing monomers, crosslinking agents, dispersants, and catalysts in a ratio of 3:1, wherein the mass ratio of monomers, crosslinking agents, dispersants, and catalysts was 8:2:1:1. The mixed slurry was then vacuum-treated to obtain MgO gel liquid.

[0120] S3. Drying and shaping

[0121] Pour the MgO gel liquid into a mold and place the mold in an oven. Dry the MgO gel liquid at 50°C for 2 hours. The gel liquid undergoes a physicochemical reaction in the mold to generate a green body with a certain strength.

[0122] S4. Dehydration and degreasing

[0123] The billet was placed in a muffle furnace and heated from room temperature to 50°C, 80°C, 120°C, and 110°C at a rate of 5°C / min, and held at each temperature for 3 hours to dehydrate the billet. Then, it was heated from 110°C to 500°C at a rate of 1°C / min and held for 2 hours to degrease.

[0124] S5. Sintering

[0125] Finally, the temperature was increased from 500℃ to 1000℃ at a rate of 5℃ / min and held for 20 min, then increased from 1000℃ to 1400℃ at a rate of 5℃ / min and held for 170–190 min. The furnace was then cooled to room temperature to obtain the MgO ceramic material prepared by low-temperature sintering.

[0126] The MgO ceramic materials prepared in Examples 1-1 and Comparative Examples 1 and 2 were subjected to performance testing. The test results are shown in Table 1 below:

[0127] Table 1

[0128]

[0129] As shown in the table, with the synergistic effect of Al2O3 and MgF2, this invention can prepare a magnesium oxide ceramic with a density of over 90% at a low sintering temperature, and it also exhibits good thermal conductivity and strength. Figure 1As shown, with increasing MgF2 content and sintering temperature, the sample density gradually increases, while the number and size of pores relatively decrease. After adding magnesium fluoride at 1400℃, from... Figure 2 Magnesium aluminate phase was found in the sample. The presence of magnesium aluminate phase reduced the number and size of pores in the MgO ceramic and increased the density of the sample.

[0130] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the implementation of the present invention. Those skilled in the art can make other variations or modifications based on the above description. It is neither necessary nor possible to exhaustively describe all embodiments here. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention should be included within the scope of protection of the claims of the present invention.

Claims

1. A MgO ceramic material prepared by low-temperature sintering, characterized in that, The raw materials include magnesium oxide, aluminum oxide, and magnesium fluoride, wherein the mass ratio of magnesium oxide, aluminum oxide, and magnesium fluoride is 95:5:3~5; the preparation steps include: S1. Mix magnesium oxide, aluminum oxide and magnesium fluoride powders evenly according to the mass ratio to obtain a mixed powder; S2. The mixed powder is mixed with organic matter to obtain a mixed slurry, and then the mixed slurry is vacuum treated to obtain MgO gel liquid, wherein the organic matter includes monomers, crosslinking agents, dispersants and catalysts; S3. After drying the MgO gel liquid, a green body is obtained, and then dehydrated at 50~160℃, and then heated to 500℃ for degreasing. S4. The degreased green body is heated to 1400~1450℃ for sintering, and after cooling, MgO ceramic material prepared by low-temperature sintering is obtained.

2. The MgO ceramic material prepared by low-temperature sintering according to claim 1, characterized in that, The mixed powder is also pretreated by removing impurities with an acidic solution and ball milling.

3. The MgO ceramic material prepared by low-temperature sintering according to claim 1, characterized in that, The mass ratio of the mixed powder to the organic matter is 2~4:

1.

4. The MgO ceramic material prepared by low-temperature sintering according to claim 1, characterized in that, The monomer is one or more of acrylic acid, dimethacrylamide, dimethylaminoisobutylene acid, methacrylate, and hydroxyethyl acrylate; the crosslinking agent is one or more of N,N-methyleneacrylamide and isocyanate; and the catalyst is one or more of tetramethylethylenediamine, Lewis acid, and polyacrylamide.

5. The MgO ceramic material prepared by low-temperature sintering according to claim 1, characterized in that, The dehydration process includes holding the water at 50℃, 80℃, 120℃ and 160℃ for 2-3 hours respectively.

6. The MgO ceramic material prepared by low-temperature sintering according to claim 1, characterized in that, During the heating and degreasing process, the temperature is maintained at 500℃ for 2-3 hours.

7. The MgO ceramic material prepared by low-temperature sintering according to claim 1, characterized in that, The heating rate for the dehydration process is 5~10℃ / min; the heating rate for the degreasing process is 1~5℃ / min.

8. The MgO ceramic material prepared by low-temperature sintering according to claim 1, characterized in that, The sintering heating rate is 1~5℃ / min, and the holding time is 2~3h.

Citation Information

Patent Citations

  • A high thermal conductivity oxide ceramic material and its preparation method

    CN104276815B

  • Method for preparing high-density magnesia ceramic

    CN102060514A

  • Y2O3-MgO nano-composite ceramic and preparation method thereof

    CN103922742A